The Use of Instagram-Integrated Learning Media on Gender-Based Student Learning Motivation in Reaction Rate Material - Widarti, Hayuni Retno; Yamtinah, Sri; Mawardi, Mawardi; Rokhim, Deni Ainur; Syafruddin, Afis Baghiz; Amalia, Elvira Risva Firda (Universitas Negeri Surabaya, 2024)
This research aims to determine the effect of using integrated learning media Instagram in increasing students' learning motivation on reaction rate material and to analyze the results of female and male students' learning motivation on reaction rate material. The method used is qualitative descriptive research. The subjects in this research were students of one of the State High Schools in Malang City class XI MIPA 2, totaling 11 male students and 20 female students who used Instagram learning media. The class is heterogeneous because it has a gender distribution with more female students than male students. The research results show that 1) The use of integrated learning media Instagram can increase students' learning motivation. 2) There is no significant difference in the comparison of the increase in male students' learning motivation.